2020
DOI: 10.1108/wje-11-2019-0333
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on influence of electrode vibrations on hardness and microstructure of 1018 mild steel weldments

Abstract: Purpose The purpose of this study is to explore the importance of vibrations during welding process. In recent years, welding has gained its supremacy in the field of production. The main set back of the welding process is induced residual stresses, which is a major cause for many welding defects. These defects can be minimized by post-weld heat treatment methods, which is a time consuming and laborious process. In the recent past, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Because of the vibratory treatment, the crystals develop in a specified direction during welding. As a result of the grain refinement, the toughness of the weldment increased by 25% [23,24]. The effects of transverse oscillation frequency and amplitude on mild-steel weldment characteristics are explored.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the vibratory treatment, the crystals develop in a specified direction during welding. As a result of the grain refinement, the toughness of the weldment increased by 25% [23,24]. The effects of transverse oscillation frequency and amplitude on mild-steel weldment characteristics are explored.…”
Section: Introductionmentioning
confidence: 99%
“…An observation in the microstructure at 12 V of weldments, the weld defects were identified which is the reason for diminished tensile strength is shown in Figure 13(a). Similarly, the electrode voltage is raised to 14 volts the voids were reduced when compared with the microstructure of the 12 V weldments is shown in Figure 13 (Bade et al, 2020). The fine grain structure is owing to the refined molten metal at fusion state with excitation at different voltages with respect to the frequencies.…”
Section: Welded Joints Microstructural Analysis At 190 V Of Vibro-motor and Different Voltages Of Dc Motormentioning
confidence: 91%
“…Mechanical excitations to the vibrating table and electrode also have a significant effect on the mechanical properties of 1018 mild steel. The authors observed that stirring of weld pool with the mechanical excitations influences the hardness and ultimate tensile strength of the 1018 mild steel properties along with the grain structure [15][16][17].…”
Section: Literature Review 21the Effect Of Vibratory Assisted Welding (Vaw)mentioning
confidence: 99%